2018
DOI: 10.1155/2018/8750464
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis in Rats Is Associated with an Inflammatory Response of the Hippocampus

Abstract: Allergic rhinitis (AR) is a major concern in personal and public health, which negatively affects emotions and behavior, leading to cognitive deficits, memory decline, poor school performance, anxiety, and depression. Several cellular and molecular mediators are released in the inflammatory process of AR and activate common neuroimmune mechanisms, involving emotionally relevant circuits and the induction of anxiety. Responsiveness of the hypothalamic-pituitary-adrenal (HPA) axis to allergic processes have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…This study also showed that AR-induced OD was closely related to neuroin ammation of the olfactory bulb. The expression of microglia marker protein CD11b, TNF-α, IL-1β and IL-6 in the olfactory bulbs were signi cantly increased in the AR mice with OD, which is similar to the ndings in the hippocampus [32]. However, the mechanism of allergen-induced damage to the olfactory bulb is not clear.…”
Section: Disccussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This study also showed that AR-induced OD was closely related to neuroin ammation of the olfactory bulb. The expression of microglia marker protein CD11b, TNF-α, IL-1β and IL-6 in the olfactory bulbs were signi cantly increased in the AR mice with OD, which is similar to the ndings in the hippocampus [32]. However, the mechanism of allergen-induced damage to the olfactory bulb is not clear.…”
Section: Disccussionsupporting
confidence: 66%
“…Several studies on humans and rodents have shown that the intranasal or nebulized inhalation in allergen-sensitized animals induced avoidance behavior and activated limbic brain areas [8,9,32,33]. OVA or pollen-induced AR rats produced TH2 cytokines in the olfactory bulb and prefrontal cortex but not in the temporal cortex and hypothalamus, and increased brain activity was observed by functional MRI [8].…”
Section: Disccussionmentioning
confidence: 99%
“…However, the study concluded that antidepressant use, not montelukast use, may be correlated with asthma severity [ 49 ]. A study using an animal allergic rhinitis model reported that allergic rhinitis was associated with the induction of an inflammatory response in the hippocampus and that it may trigger associated neuropsychiatric events [ 50 ]. These findings do not guarantee the safety of montelukast; therefore, clinicians should consider the benefits and risks of montelukast before prescribing it.…”
Section: Safety Profilementioning
confidence: 99%
“…Allergic rhinitis (AR) is a chronic inflammatory disorder of the nasal mucosa, which is characterized by the presence of one or some symptoms, including itchiness, sneezing, rhinorrhea, nasal congestion, and daily alterations in sense of olfaction [1–4]. AR is a highly prevalent chronic disease that affects 400 million people worldwide; and epidemiological studies have reported that 20–30% of adults and 40% of children suffer from AR [57].…”
Section: Introductionmentioning
confidence: 99%